Potent halogenated xanthone derivatives: synthesis, molecular docking and study on antityrosinase activity - Baharuddin, Fatin Farhana; Mad Nasir, Nadiah; Tejo, Bimo Ario; Koh, Soo Peng; Ramakrishnan, Shuruti; Nordin, Nur Qurratu Ain A.; Adzahar, Anis Nasuha; Devakrishnan, Pavithren; Mohd Razib, Salsabiilaa (Taylor and Francis Group, 2023)
Tyrosinase inhibitors can reduce melanin production for skin whitening, but some existing products may harm the skin. This study discovered six compounds that inhibit tyrosinase in the mushroom Agaricus bisporus by over 50%. Compound 11 displayed strong inhibition (92.2% and 86.7%) for L-tyrosine and L-DOPA substrates, while compound 13 showed high inhibition (96.0% and 62.0%) for both substrates. Molecular docking simulations revealed compounds 11 and 13 bind at the allosteric site of the enzyme. Xanthone derivatives, based on these findings, hold potential as safe skin whitening agents and for pigmentation-related diseases in the cosmetic industry.